Terson Syndrome: what an ophthalmologist should know? Poster Presentation - Case Report - Ophthalmologist - ANINDITA WICITRA; Muhammad Firdaus (Majalah Oftalmologi Indonesia, 2023)
Abstract Introduction : Terson syndrome is the occurrence of any intraocular hemorrhage in patients with intracranial hemorrhage or traumatic brain injury. In this article we present a case of patient with Terson Syndrome after craniotomy. Case Illustration : Forty-six yo female patient consulted from neurosurgery department with chief complain of blurry vision in both eyes since 1 day before. Pain or red eyes were denied. There was no history of visual field defect. She had history of breast cancer and she underwent craniotomy four days before because of her brain metastases. Her Glasgow Coma Scale was 15. In ophthalmology examination, her visual acuity is 6/6 with correction in both eyes with good ocular motility. RAPD was positive in her left eye, and posterior segment showed bilateral optic disc edema with intrapapillary and peripapillary hemorrhage. Humphrey examination revealed enlargement of blind spot in the right eye. Brain CT Scan demonstrated hemorrhagic lesion with pneumoencephal within post operative defect area in right parietal lobe. Laboratory examination showed normal fibrinogen and thrombocyte aggregation with elevation of d-dimer. After two weeks observation, visual acuity still 6/6 in both eyes with decreasing intrapapillary and peripapillary hemorrhage. Discussion : The exact pathophysiology of Terson Syndrome is still unknown. Even though, it has association with high intracranial pressure. Patient with Terson Syndrome will develop 5 times higher mortality rate compare to subarachnoid hemorrhage without Terson Syndrome. Conclusion : Terson Syndrome needs to be recognized early since it will bring significant prognostic effect and cause permanent vision loss if left untreated